Misfits, Mavericks and Mainstreams: Drivers of Innovation in the Creative Industries. Issue 6 (June 2016) - Jones, Candace; Svejenova, Silviya; Pedersen, Jesper Strandgaard; Townley, Barbara
Creative industries are among the fastest-growing and most important sectors of European and North American economies. Their growth depends on continuous innovation, which is important in many industries and also challenging to manage because of inherent tensions. Creative industries, similar to many industries, depend not only on novelty to attract consumers, but also on familiarity to aid comprehension and stabilize demand for cultural products. Agents in the creative industries play with these tensions, generating novelty that shifts industries' labels and boundaries. This tension and agency makes them a valuable setting for advancing theoretical ideas on who drives innovation, from mavericks that challenge conventions to mainstreams that build upon them. We trace this history and then turn to the five papers in the special issue, which examine in depth how mavericks, misfits, mainstreams and amphibians in various creative domains, from artistic perfumery to choreography, engage with innovation and address tensions. These processes of innovation point to future research that explores and exploits the role of materiality in meaning making, the role of capitals in translation processes and the dynamics of value and evaluation.